Legal Protection Of Finance Companies Through The Withdrawal Of Fiduciary Guarantee Objects in Multipurpose Financing Agreements - Habibah Indah Sebayang (Universitas Sumatera Utara, 2023)
A finance company is a form of business in the non-bank financial sector which is carried out in the form of providing funds or capital goods and in conducting financing requires the existence of a guarantee, namely the motorized vehicle itself as collateral. Finance companies as creditors require a guarantee from the debtor. The formulation of the problem in this study is how to withdraw fiduciary guarantee objects in multipurpose financing agreements for motorized vehicles at finance companies, how is the legal protection for finance companies in consumer financing business activities in multipurpose financing agreements for motorized vehicles.The method used in this thesis research is descriptive normative legal research. The approach method used is the case approach. The data sources used consist of secondary data and are supported by primary legal materials, secondary legal materials and tertiary legal materials. Writing research through regulations and legal materials related to this research.The results of the study explain that the withdrawal of fiduciary guarantee objects in multipurpose financing agreements for motorized vehicles at finance companies can be carried out parate executie to objects of fiduciary guarantees. Legal protection for finance companies in consumer financing business activities in multipurpose financing agreements for motorized vehicles is carried out preventively or repressively.